The Effects of Cannabinoids on Sleep - Bhanu Prakash Kolla; Lisa Hayes; Chaun Cox; Lindy Eatwell; Mark Deyo-Svendsen; Meghna P. Mansukhani (SAGE Publishing, 2022)
The use of cannabis products to help with sleep and various other medical conditions by the public has increased significantly in recent years. Withdrawal from cannabinoids can lead to sleep disturbance. Here, we describe a patient who developed significant insomnia leading to worsening anxiety, mood, and suicidal ideation in the setting of medical cannabis withdrawal, prompting presentation to the Emergency Department and inpatient admission. There is a limited evidence base for the use of cannabis products for sleep. We provide a comprehensive review evaluating the literature on the use of cannabis products on sleep, including an overview of cannabis and related psychoactive compounds, the current state of the law as it pertains to the prescribing and use of these substances, and potential side effects and drug interactions. We specifically discuss the impact of cannabis products on normal sleep and circadian sleep-wake rhythms, insomnia, excessive daytime sleepiness, sleep apnea, parasomnias, and restless legs syndrome. We also describe the effects of cannabis withdrawal on sleep and how this increases relapse to cannabis use. Most of the studies are observational but the few published randomized controlled trials are reviewed. Our comprehensive review of the effects of cannabis products on normal sleep and sleep disorders, relevant to primary care providers and other clinicians evaluating and treating patients who use these types of products, shows that cannabis products have minimal to no effects on sleep disorders and may have deleterious effects in some individuals. Further research examining the differential impact of the various types of cannabinoids that are currently available on each of these sleep disorders is required.